Arahan Pola Distribusi Pemasaran Kopi Pada Warung Kopi dan Kafe di Kota Makassar - Abuzard Ghifari; Ihsan Ihsan; Laode Muh. Asfan Mujahid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
The growth of coffee in Makassar City is very rapid with the proliferation of coffee shops and kafes with different concepts, where the distribution of coffee is very influential in ensuring the stock or ingredients of coffee in each coffee shop. This study aims to: (1) determine the distribution conditions of coffee distribution in coffee shops and kafes in Makassar City; (2) Knowing the distribution flow and differences in coffee prices from the area of ​​origin to the area of ​​the supplier; (3) Knowing the strategy to increase the efficiency of coffee distribution in Makassar City. The analytical technique used is SWOT analysis and distribution. Determination of the sample in this study was carried out using the Non-Probability Sampling technique with the Quota Sampling technique. This study took 5 samples from coffee shops and 5 samples from kafes in each district. Based on the results of the research, the distribution of coffee beans in the majority of kafes or coffee shops comes from the Tana Toraja, Enrekang, and coffee shops in Makassar. The distribution flow of coffee beans is divided into two patterns with the difference in price margins between the two distribution patterns of 50,000. Based on the results of the SWOT analysis, strategic ideas emerged, namely utilizing the development of marketing networks, improving service quality, increasing promotional and advertising activities, setting prices to face competition, increasing the use of technology, and suppressing any possible leakage of operational costs.